Living Hadith in the Practice of Distancing the Line (Ṣaff) in Congregational Prayers during Corona Pandemic - Ahmad Syahid (Jurnal Living Hadis, 2020)
This is descriptive, qualitative research that explains the practice of distancing the lines (ṣaff) in congregational prayers during the corona pandemic. This research employs phenomenological perspective to do the analysis on the data, particularly the interviews published in online media. Another side of the analysis is the inductive and deductive technique. This research focuses on the ways in which that practice is put into action, the underlying factors, and the impact it poses to the society, particularly the way they face the pandemic. It argues that the practice is a sort of realization of physical distancing to prevent the spreading of the virus and at the same time the real attempt of Indonesian Muslims to observe one of the principal goals of sharia, that is al-muḥāfaẓa ‘alā an-nafs.